Mortality and its predictors in patients with rheumatoid arthritis: a Danish population-based inception cohort study. (3rd September 2018) - Pedersen, JK; Holst, R; Primdahl, J; Svendsen, AJ; Hørslev-Petersen, K
Abstract : Objectives : To investigate mortality and its predictors in a retrospectively defined population-based rheumatoid arthritis (RA) inception cohort Method : We included patients ascertained with incident RA from a region in the southern part of Denmark from 1995 to 2002. All patients fulfilled the 1987 American College of Rheumatology criteria for RA. The patients were followed from RA classification until death, emigration, or end of follow-up on 31 December 2013. We used personal record linkage with national public registers to obtain information on education, employment, cohabitation, comorbidity, and vital status. Results : The cohort comprised 509 patients, of whom 200 (39%) died during 6079 person-years. The most frequent underlying causes of death were cardiovascular disease (34%), neoplasms (26%), and respiratory disease (12%). In rheumatoid factor (RF)-positive males, the standardized mortality ratio (95% confidence interval) from all causes was 1.47 (1.15–1.88), from cardiovascular disease 1.63 (1.09–2.46), from respiratory disease 2.03 (1.06–3.90), and from neoplasms 2.26 (1.02–5.03) in the age group < 70 years, and 2.45 (1.23–4.90) in the age group > 79 years. On applying Cox models after multiple imputations by chained equations, we found that RF modified the effect of age. Employment status, comorbidity, and gender were independent baseline predictors of subsequent mortality. Conclusion : In this cohort, significant excess mortality was confined to RF-positive males. The effect of age was modified by RF, and employment status and comorbidity were independent predictors of mortality.